Legal Guarantees and Inconsistency of State Recognition to the Right of Religion/Belief in Indonesia - Kadarudin, Kadarudin (Faculty of Law, Hasanuddin University, 2015)
The right to freedom of religion/belief has been guaranteed by law in Indonesia, but there are still going on some violations of the right to freedom of religion/belief in the various regions. The purpose of this study was to determine the form of the legal guarantee of the right to freedom of religion/belief in Indonesia, shape inconsistencies state recognition of the right to religion/belief in Indonesia, and efforts to improve the rights of religion/belief in Indonesia. This paper uses a normative study. It was found that there are some rules that apply in Indonesia, which may hinder the implementation of the right of religion/belief, thus causing the occurrence of cases of rights violations religion/belief in some areas, should therefore rules should be immediately revoked. The conclusions of this paper are contained inconsistent state recognition of the right to religion/ belief in Indonesia.